Process-oriented metrics to provide feedback and assess the performance of students who are learning surgical procedures: The percutaneous dilatational tracheostomy case. (2nd November 2022) - Martínez, Juan José; Galvez-Yanjari, Víctor; de la Fuente, Rene; Kychenthal, Catalina; Kattan, Eduardo; Bravo, Sebastián; Munoz-Gama, Jorge; Sepúlveda, Marcos
Abstract: Purpose: Assessing competency in surgical procedures is key for instructors to distinguish whether a resident is qualified to perform them on patients. Currently, assessment techniques do not always focus on providing feedback about the order in which the activities need to be performed. In this research, using a Process Mining approach, process-oriented metrics are proposed to assess the training of residents in a Percutaneous Dilatational Tracheostomy (PDT) simulator, identifying the critical points in the execution of the surgical process. Materials and methods: A reference process model of the procedure was defined, and video recordings of student training sessions in the PDT simulator were collected and tagged to generate event logs. Three process-oriented metrics were proposed to assess the performance of the residents in training. Results: Although the students were proficient in classic metrics, they did not reach the optimum in process-oriented metrics. Only in 25% of the stages the optimum was achieved in the last session. In these stages, the four more challenging activities were also identified, which account for 32% of the process-oriented metrics errors. Conclusions: Process-oriented metrics offer a new perspective on surgical procedures performance, providing a more granular perspective, which enables a more specific and actionable feedback for both students and instructors.